Comment on ＂Variational Iteration Method for Fractional Calculus Using He's Polynomials - He, Ji-Huan (Abstract and Applied Analysis, 2012)
Recently Liu applied the variational homotopy perturbation method for fractional initial boundary value problems. This note concludes that the method is a modified variational iteration method using He’s polynomials. A standard variational iteration algorithm for fractional differential equations is suggested.